A Hidrocloroquin tatalaksana COVID-19, Apakah sudah tepat dan adakah alternatif lain? - Mohammad Ridho Devantoro (JIMKI: Jurnal Ilmiah Mahasiswa Kedokteran Indonesia, 2020)
There has been a pandemic phenomenon known as COVID-19, but WHO has not yet established a medical management guidelines for the disease. a lot of debate about the use of hydrocloroquine / cloroquin with various in vitro studies and some drugs such as anti-inflammatory proposed to be an alternative therapy with a combination therapy mechanism because it is more effective than monotherapy.